TOWARDS DIGITAL TRANSFORMATION: DEVELOPMENT OF A DIGITAL SKILLS FRAMEWORK FOR PUBLIC OFFICERS - Shuib, Nor Liyana Mohd; Anwar, Nurul Ain Khairul; Shuib, Nor Atiqah Mohd; Badari, Khairatul Alyani (Malaysian Journal of Computer Science, 2024)
This study aims to develop a comprehensive Digital Skills Framework for public officers to support Malaysia’s digital transformation. Using a quantitative approach, expert validation confirmed the relevance of key components such as digital literacy, communication, problem-solving, and digital security (S-CVI/Ave of 0.94). The framework addresses the need for structured digital skills development to enhance public officers’ effectiveness in a digital environment. While limited by its reliance on expert validation, the framework provides practical guidance for designing training programs, improving public service delivery, and supporting the state’s digital agenda, contributing to more transparent and efficient governance.